Ilmu Laduni Perspektif Psikologi Pendidikan - Eko Harianto (Journal Khafi : Journal Of Islamic Studies, 2023)
Laduni knowledge is an inner science received directly through intuition or inspiration from God. Laduni knowledge is divided into knowledge obtained without learning stages (wahbiy) and knowledge obtained through learning efforts (kasbiy). This type of research includes library research, namely examining literature sources related to the subject matter of the investigation. Laduni science is also part of the psychology discipline that studies psychiatric problems in education. In psychology, laduni is known as intuition. Intuitive knowledge is different from the concept of inner and outer. Intuition is the ability to understand something without rational and scientific thinking; this understanding arises suddenly from consciousness